Reduced Bordetella pertussis-specific CD4+ T-Cell Responses at Older Age - Lambert, Eleonora E.; van Twillert, Inonge; Beckers, Lisa; Poelen, Martien C. M.; Han, Wanda G. H.; Pieren, Daan K. J.; van Els, Cécile A. C. M. (Frontiers in Aging, 2022)
Pertussis, a human-specific respiratory infectious disease caused by the Gram-negative bacterium Bordetella pertussis (Bp), remains endemic with epidemic years despite high vaccination coverage. Whereas pertussis vaccines and natural infection with Bp confer immune protection, the duration of protection varies and is not lifelong. Recent evidence indicates a considerable underestimation of the pertussis burden among older adults. Whereas the impact of increasing age on Bp-specific humoral immunity has been demonstrated, little is known on immunosenescence of CD4+ T-cell responses in the context of Bp. Here, we aimed to address whether increasing age impacts responsiveness of the Bp-specific CD4+ T-cells in the memory pool following a clinically symptomatic pertussis infection in whole cell vaccine-primed pediatric and adult cases. Cytokine and proliferative responses and phenotypical profiles of CD4+ T cells specific for Bp antigens at an early and late convalescent timepoint were compared. Responses of various Th cytokines, including IFNγ, were significantly lower in older adults at early and late timepoints post diagnosis. In addition, we found lower frequencies of Bp-specific proliferated CD4+ T cells in older adults, in the absence of differences in replication profile. Phenotyping of Bp-specific CD4+ T cells suggested reduced expression of activation markers rather than increased expression of co-inhibitory markers. Altogether, our findings show that the magnitude and functionality of the Bp-specific memory CD4+ T-cell pool decrease at older age. Declined CD4+ T-cell responsiveness to Bp is suggested to contribute to the burden of pertussis in older adults.